2013
DOI: 10.1007/978-3-642-35879-1_43
|View full text |Cite
|
Sign up to set email alerts
|

ICTs in Special Education: A Review

Abstract: Abstract. The use of information communication technologies (ICTs) in a special educational needs (SEN) environment has gathered accumulative evidence around it during the last decade (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). In many settings ICT has become an important element of the learning and teaching process. ICT assessment tools can better recognize and integrate learning difficulties across students, while computer-based intervention tools can play a significant role in a child's li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…The results of this method indicated that this could be effective in the remediation of dyscalculia, for children aged 7-8 and under. [22] Sean, a 15-year-old pupil living in the south of England finds a computer with a separate wireless screen to be a vital part of his education. He has been profoundly deaf from birth but is a high achiever and already has a grade C in math.…”
Section: Touch-sensitive Screensmentioning
confidence: 99%
“…The results of this method indicated that this could be effective in the remediation of dyscalculia, for children aged 7-8 and under. [22] Sean, a 15-year-old pupil living in the south of England finds a computer with a separate wireless screen to be a vital part of his education. He has been profoundly deaf from birth but is a high achiever and already has a grade C in math.…”
Section: Touch-sensitive Screensmentioning
confidence: 99%
“…Nowadays, visually impaired students can take advantage of a large number of effective assistive technologies besides, they often encounter a number of different accessibility and usability problems [2] . According to the World Health Organization about 314 million individuals are visually impaired worldwide.…”
Section: Sensory and Physical Impairmentsmentioning
confidence: 99%
“…Memory skills of children with special needs have been a domain of great research for professionals over the last years as there is evidence that shows that poor memory skills characterize children who fail to progress normally in different areas of needs PAPER ICTS AND SPECIAL EDUCATION IN KINDERGARTEN [2].However, it is well known that computerized programs seem to be a promising new approach to memory interventions.…”
Section: Children With Memory Problemsmentioning
confidence: 99%
See 2 more Smart Citations